2001
DOI: 10.1097/00054725-200102000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Saccharomyces Cerevisiae Antibodies (ASCA), Phenotypes of IBD, and Intestinal Permeability: A Study in IBD Families

Abstract: ASCA is strongly associated with familial CD in Belgium, and 21% of healthy family members also display the marker. The association is much weaker in patients belonging to mixed families. ASCA is a stable marker and is not a secondary phenomenon due to increased intestinal permeability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
102
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(113 citation statements)
references
References 37 publications
9
102
2
Order By: Relevance
“…20 This group, however, only included patients on medical therapy and did not observe patients post-operatively. Interestingly, Vermeire et al could not associate ASCA serum levels with the degree of intestinal permeability in patients with CD as measured by 51Cr-EDTA intestinal permeation, 21 which supports the hypothesis that loss of tolerance towards Saccharomyces cerevisiae in CD is independent of a breach of intestinal integrity. Concordantly, in our cohort there was neither a difference in ASCA seropositivity nor ASCA serum levels in patients experiencing mild vs. severe post-operative endoscopic recurrence.…”
Section: Discussionmentioning
confidence: 84%
“…20 This group, however, only included patients on medical therapy and did not observe patients post-operatively. Interestingly, Vermeire et al could not associate ASCA serum levels with the degree of intestinal permeability in patients with CD as measured by 51Cr-EDTA intestinal permeation, 21 which supports the hypothesis that loss of tolerance towards Saccharomyces cerevisiae in CD is independent of a breach of intestinal integrity. Concordantly, in our cohort there was neither a difference in ASCA seropositivity nor ASCA serum levels in patients experiencing mild vs. severe post-operative endoscopic recurrence.…”
Section: Discussionmentioning
confidence: 84%
“…The markers studied most are intestinal permeability, and a number of anti-microbial antibodies: anti-Saccharomyces cerevisiae antibodies (ASCA) and atypical pANCA (perinuclear antineutrophil cytoplasmic antibodies). [11][12][13][14][15] Other microbial antibodies found in IBD patients as antiOmpC (directed against the outermembrane porin C of Escherichia coli), I2 (antibodies directed against Pseudomonas fluorescens) and Cbir 1 (anti-flagellin antibodies) have not been studied in asymptomatic family members. [16][17][18] However, the presence of these subclinical markers has no clinical implications yet and longitudinal studies are needed first to evaluate their exact meaning.…”
Section: Genetic Epidemiologymentioning
confidence: 99%
“…It was, thus, concluded that ASCA may result from a mucosal permeability defect. However, Vermeire et al [20] were not able to show a correlation between ASCA and intestinal permeability.…”
Section: Introductionmentioning
confidence: 89%